Pengaruh Disiplin Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Mediasi - Windi Windi; Qomariah Lahamid (SYNERGY: Jurnal Bisnis dan Manajemen, 2024)
This research was conducted at CV. Delta Sukses Jaya Duri. The aim of this research is to determine the effect of work discipline on employee performance with job satisfaction as an intervening variable on CV. Delta Sukses Jaya Duri. The sample in this study was 34 employees using the census or saturated sampling method. This research uses quantitative analysis and description using the path analysis method and the data is analyzed using the Smart-PLS program. The results of this study show that work discipline has a significant effect on job satisfaction at CV. Delta Sukses Jaya Duri with a calculated t value (3.957) less than t table (1.650) with a P Value more than 0.06. Work discipline has a significant effect on employee performance, with a t calculated value (3.459) less than t table (1.650) with a P Value more than 0, 05 shows that work discipline has a significant effect on employee performance, with a t value (0.195) less than t table (1.650) with a P value more than 0.05, then job satisfaction does not have a significant effect on employee performance with a t value (0.174) more than t table (1.650) with P Value less than 0.05, work discipline does not have a significant effect on employee performance mediated by job satisfaction. And based on the R-Square calculation, it is 55% and the rest is influenced by other variables.